The Role of Adaptive Reuse in Revitalizing Abandoned Buildings in Malaysia - Nur Husnina Ngisa; Ismail, Sushilawati (Journal of Structural Monitoring and Built Environment, 2026)
In the context of urban development constraints, adaptive reuse of abandoned buildings in Malaysia presents a promising opportunity. While abandoned buildings contribute to significant economic and environmental challenges, they also hold considerable potential for revitalization through adaptive reuse projects. This study explored the key factors influencing the adaptive reuse of buildings and the challenges encountered in such initiatives. The primary aim was to examine the role of adaptive reuse in revitalizing abandoned buildings in Malaysia. Employing a Delphi study approach, data was collected from industry professionals through a questionnaire survey, which identified the factors and challenges associated with adaptive reuse projects. The study revealed several key consideration factors, including government incentives, originality, actors in decision-making, environmental and architectural merit, and social interest. Additionally, it highlighted critical challenges, such as maintenance issues, building code compliance, constraints in building performance, complications arising from multiple ownership, and uncertainties regarding renovation processes. The findings provide valuable insights and recommendations for policymakers, developers, and urban planners, advocating for a sustainable urban development model that leverages adaptive reuse to enhance economic resilience and environmental preservation in Malaysia. The study’s limitations include a narrow focus on the Malaysian context and the reliance on expert opinions, which may not fully capture the perspectives of all stakeholders. Future research could address these limitations by broadening the scope to include more diverse perspectives and exploring additional case studies in different regions.